Synthesis of Sulfated Chitosan Through Sulfation Reaction of Chitosan with Chlorosulfonic Acid in N, N-Dimethylformamide, and Antibacterial Activity Test - Manik, Epria R; Kaban, Jamaran (Talenta Publisher, 2022)
Sulfated chitosan has been successfully synthesized through sulfation reaction between chitosan and chlorosulfonic acid using catalyst and N, N-Dimethylformamide (DMF) solvent. The first step was sulfation of chitosan with 4; 4.5; 5 mL of HClSO3. The formation of sulfated chitosan was supported by an increased solubility in water and the appearance of peaks at 1111 cm-1, which indicated the C-O-S group. Sulfated chitosan that has been produced, has a degree of sulfation of 5.6041%; 6.0045%; 6.8051%. Sulfated chitosan shows moderate antibacterial activity and a wide spectrum of antibacterial properties against Escherichia coli and Staphylococcus aureus bacterias. The increase in the degree of sulfation was proportional to the increase in antimicrobial activity of both bacteria. The highest antibacterial activity based on inhibitory zone diameter was 10 mm for sulfated chitosan that has been produced from 1 g of chitosan with 5 mL of HClSO3 with a degree of sulfation was 6.8051%.